Dosimetric impact of contouring and needle reconstruction uncertainties in US-, CT- and MRI-based high-dose-rate prostate brachytherapy treatment planning. Issue 1 (April 2017) - Rylander, Susanne; Buus, Simon; Pedersen, Erik M.; Bentzen, Lise; Tanderup, Kari
Abstract: Background and purpose: The purpose was to evaluate the dosimetric impact of target contouring and needle reconstruction uncertainties in an US-, CT- and MRI-based HDR prostate BT treatment planning. Material and methods: US, CT, and MR images were acquired post-needle insertion in 22 HDR-BT procedures for 11 consecutive patients. Dose plans were simulated for an US-, CT- and MRI-based HDR-BT treatment planning procedure. Planning uncertainties in US- and CT-based plans were evaluated using MRI-based planning as reference. Target (CTVProstate ) was re-contoured on MRI. Dose results were expressed in total equivalent dose given in 2 Gy fractionation dose for EBRT (46 Gy) plus 2 HDR-BT fractions. Results: Uncertainties in US- and CT-based planning caused the planned CTVProstate -D90% to decrease with a mean of 2.9 ± 5.0 Gy ( p = 0.03) and 2.9 ± 2.9 Gy ( p = 0.001), respectively. The intra-observer contouring variation on MRI resulted in a mean variation of 1.6 ± 1.5 Gy in CTVProstate -D90% . Reconstruction uncertainties on US resulted in a dose variation of ±3 Gy to the urethra, whereas data for CT were not available for this. Conclusions: Uncertainties related to contouring and reconstruction in US- and CT-based HDR-BT treatment plans resulted in a systematic overestimation of the prescribed target dose. Inter-modality uncertainties (US and CT versus MR) were larger than MR intra-observer uncertainties.